The Development of Book Creator Assisted Learning E-Modules in the Curriculum Merdeka on Plants as the Source of Life on Earth at Grade IV Elementary School - Muhammad Subhan; Dian Estu Prasetyo; Aprilia Puspita (The Future of Education Journal, 2024)
This study is motivated by the lack of adequate teaching materials, which leads to students struggling to understand the learning material, feeling bored during lessons, and finding the teaching materials unattractive. Additionally, students tend to have an audio-visual learning style. Therefore, it is necessary to develop teaching materials that can assist students in the learning process, enhancing their understanding of the IPAS (Science, Social Science, and Arts) subject. The aim of this study is to produce a valid, practical, and effective e-module for Book Creator in the Merdeka Curriculum on the topic "Plants as the Source of Life on Earth" for Grade 4 elementary school students. This research is a Research and Development (R&D) study using the ADDIE development model, which consists of the phases: analyze, design, development, implementation, and evaluation. The subjects of the trial were students of Grade IV SD Negeri 05 Sitiung. The data collection instruments used were assessment sheets for validation, practicality, and effectiveness. These instruments were validated by three validators: material, language, and graphic validators. The results of the validation conducted by the three validators showed a final validation score of 85.56%, categorized as highly valid. The practicality score from teacher responses was 92.85%, categorized as very practical, and the student responses showed a score of 84.59%, also categorized as very practical. The effectiveness score from student learning outcomes was 85.71%, categorized as highly effective for improving student learning outcomes.